Village funds and poverty reduction in Indonesia: new policy insight - Choirul Anam; Michal Plaček; Vladislav Valentinov; Cristina Del Campo (Discover Global Society, 2023)
This short communication describes the current experience of implementing village funds in Indonesia, with an emphasis on the impact on poverty reduction. The authors' field observation is complemented by structured interviews and regression analysis. Our findings suggest that the potential of village funds is not fully realized. We point out that officials underestimated the significance of bottlenecks related to the capacity of local governments, to the implementation of coordination mechanisms, and to the installation of feedback mechanisms, each of which critically hinge on administrative and technical policy processes. At the same time, we felt that the officials overestimated the importance and effectiveness their own political agendas promoting community empowerment and corruption prevention.
Keywords: 320